Remittances and the household's expenditures on health - Valero Gil, Jorge Noel (Center for Business and Economic Research, Sam Houston State University, 2009)
This paper considers the effect of remittances on the share of health expenditures to total household expenditure. The main purpose of this paper is to investigate whether remittances are especially targeted towards household’s health in Mexico. We use a Tobit model with random effects and find a statistically significant effect of remittances on the proportion of health expenditures for households that do not have access to employment’s medical insurance: Our results suggest that around 10% of changes in remittances are devoted to health expenditure